Managing employee commitment through human resource practices and AMO model: A study among Gen Y SMEs employees / Norzanah Mat Nor, Elaina Rose Johar and Roshidi Hassan - Mat Nor, Norzanah; Johar, Elaina Rose; Hassan, Roshidi (UiTM Cawangan Johor, 2019)
Researchers and practitioners have been very enthusiastic and spend the most determinations to study all possible means in order to grab the most advantage from their human resources especially the Gen Y employees. These employees are pertinent to the part of organisation’s strategic business plan and contribute to the organisation’s performance as well as sustainable competitive advantage. Hence, employee commitment remains a key challenge especially in small and medium enterprises (SMEs) in Malaysia. The purpose of this paper is to investigate the relationship of compensation, training, employee involvement as well as the ability, motivation and opportunity (AMO) model towards employee commitment. The study also seeks to provide the theory-based empirical evidence that the role of AMO model as a mediator in achieving the commitment of employees and used Social Exchange Theory (SET) in order to explain the theoretical rationale of the study model. A total of 168 Gen Y employees representing SMEs service sectors in Selangor participated in this study. PLS-SEM was utilised in order to explain the relationship among human resource practices towards employee commitment as well as AMO model as a mediator. A key finding that emerged from the analysis showed that only training has direct relationship toward the employee commitment and AMO model plays an important role in gaining employee commitment as it mediates the relationship of employee involvement. However, compensation has no effect in any relationship. The research study undoubtedly provided in-depth understanding that the AMO model plays an important role in increasing the employee’s commitment to organisations and emphasises the value of AMO model in their workplace practices.